COST ESTIMATE FOR THE MONTHLY SET UP AND OPERATION OF A TELECONSULTATION ROOM - Tallita Mello Delphino; Rosimere Ferreira Santana; Julianna Nogueira Rodrigues; Keila Mara Cassiano (Cogitare Enfermagem, 2023)
Objective: to estimate the cost of setting up and monthly operation of a teleconsultation room.